Understanding the Role of Cooperative Learning Groups in Reducing Speaking Anxiety among EFL Students - Putri Alivia; Feri Ferdianto; Nina Agus Hariati (Journal of English Language and Education, 2026)
This study aims to examine the role of cooperative learning groups in reducing speaking anxiety among EFL students at SMPN 2 Gading. This study employed a qualitative descriptive research design involving 18 ninth-grade students selected through purposive sampling. Data were collected through classroom observations, questionnaires, and documentation during three cooperative learning sessions. Data were analysed using thematic analysis based on the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The findings indicate that students initially experienced high levels of speaking anxiety, characterized by hesitation, low self-confidence, and fear of negative judgment. However, after participating in cooperative learning groups, students became more comfortable, active, and confident in speaking. The main factors contributing to the reduction in anxiety included peer support, sharing opinions, emotional comfort, frequent speaking practice, and shared responsibility. This study concludes that cooperative learning is an effective pedagogical strategy for reducing speaking anxiety and creating a supportive learning environment in English as a Foreign Language (EFL) classroom.